Toward integration of knowledge based systems and knowledge discovery system - Rancan, Claudio Jorge
This paper presents a proposal for an architecture that integrates knowledge discovery systems (automatic acquisition) and knowledge based systems (experts systems). This work formulates considerations over the viability of the implementation of this architecture according to the advance of the technologies involved.